Pengaruh Gaya Hidup dan Lokasi Terhadap Keputusan Pembelian Lakosa Coffee Pekanbaru - Umli Dwi Putri; Mashur Fadli (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Lakosa Coffee is one of the coffee shops in Pekanbaru. Lakosa Coffee must be able to maintain and increase the number of consumers because it affects the company's profit. This study aims to determine and explain the influence of lifestyle (X1) and location (X2) on purchasing decisions (Y). This research method is a quantitative method. Based on the results of the partial analysis, lifestyle has a positive effect on purchasing decisions for Lakosa Coffee Pekanbaru. Then, partially, location has a positive effect on purchasing decisions for Lakosa Coffee Pekanbaru. And the F test shows that there is a simultaneous relationship between variables X and Y because the F count value> F table. The R Square result is 0.595, this value shows that 59.5% of lifestyle and location have an influence on purchasing decisions for Lakosa Coffee Pekanbaru, where the remaining 40.5% are influenced by variables not used in this study.